The experience of spatial interaction: Conceptualizing the user experience of virtual environments - Rizopoulos, Charalampos; Charitos, Dimitris (My University, 2014)
This paper examines the issue of User Experience (UX) as applied to immersive Virtual Reality from the standpoint of environmental psychology and related fields as a complement to principles from the fields of product design, psychology of emotion, formal aesthetics etc. Partly on account of its generality, multidisciplinary nature, and broad applicability, UX continues to defy a single commonly accepted definition, a fact which necessitates a holistic treatment of the subject of spatial interaction design. Various approaches and models of environmental psychology, as well as approaches to usability and UX are outlined in light of the need to highlight the influence and effects of particular spatial designs to particular dimensions of UX. Additionally, the concept and constituent dimensions of environmental appraisal are similarly defined and analysed, and indicative experimental designs currently under development are briefly described.
Keywords: Environmental appraisal; Spatial cognition; User Experience; Virtual environments